How does heat stress affect sponge microbiomes? Structure and resilience of microbial communities of marine sponges from different habitats - De Castro-Fernández, Paula; Ballesté, Elisenda; Angulo-Preckler, Carlos; Biggs, Jason; Avila, Conxita; García-Aljaro, Cristina (Frontiers in Marine Science, 2023)
Introduction Sponges are key components of marine benthic communities, providing many ecosystem functions and establishing close relationships with microorganisms, conforming the holobiont. These symbiotic microbiotas seem to be host species-specific and highly diverse, playing key roles in their sponge host. The effects of elevated seawater temperature on sponges and their microbiota are still poorly known, and whether sponges from polar areas are more sensitive to these impacts respect to temperate and tropical species is totally unknown. Methods We analyzed the microbiomes of different sponge species in their natural habitat and after exposure to heat stress in aquaria by 16S rRNA amplicon sequencing to (1) characterize the sponge microbiota covering a latitudinal gradient (polar, temperate and tropical environments), and (2) asses the effects of thermal stress on their microbial communities. Results Bacterial communities’ structure was different in the different sponge species and also respect the surrounding seawater. The core microbiome is maintained in most sponge species after a heat stress, although whether they would recover to the normal conditions previous to the stress remains yet to be further investigated. We observed increased abundances of transient bacteria from unknown origin in sponge species exposed to heat stress. Discussion Some of the transient bacteria may be opportunistic bacteria that may benefit from the heat stress-associated dysregulation in the sponge by occupying new niches in the holobiont. According to our results, sponges from Antarctic waters could be more resilient than tropical and temperate sponges. Both the microbiome composition and the changes produced by the heat stress seem to be quite host species-specific, and thus, depend on the sponge species. Under a global change scenario, the microbiomes of the tropical and temperate sponges will probably be those suffering the most the heat stress, and therefore the effects of global change may be dramatic for benthic ecosystems since sponges are a fundamental part of them.